2023
DOI: 10.1021/acs.bioconjchem.3c00085
|View full text |Cite
|
Sign up to set email alerts
|

Propensities of Fatty Acid-Modified ASOs: Self-Assembly vs Albumin Binding

Abstract: We conducted a biophysical study to investigate the self-assembling and albumin-binding propensities of a series of fatty acid-modified locked nucleic acid (LNA) antisense oligonucleotide (ASO) gapmers specific to the MALAT1 gene. To this end, a series of biophysical techniques were applied using label-free ASOs that were covalently modified with saturated fatty acids (FAs) of varying length, branching, and 5′/3′ attachment. Using analytical ultracentrifugation (AUC), we demonstrate that ASOs conjugated with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Despite the tight complex that L15 and PS-L15 can form with the MALAT1 SL (Figures 2B,C and 3B,C), it is not strong enough to counteract the cellular degradation machinery, because our cell-based assays showed that the levels of MALAT1 are reduced (Figure 5A). Additionally, compound 5 [32,46], 4001-6000 [38,45] and nts 2001-4000 [38] on mouse MALAT1. Gapmer ASOs targeting human MALAT1 nts 6001-8000 [40] and mouse MALAT1 nts 1-2000 [34,42], 2001-4000 [39], 4001-6000 [38].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Despite the tight complex that L15 and PS-L15 can form with the MALAT1 SL (Figures 2B,C and 3B,C), it is not strong enough to counteract the cellular degradation machinery, because our cell-based assays showed that the levels of MALAT1 are reduced (Figure 5A). Additionally, compound 5 [32,46], 4001-6000 [38,45] and nts 2001-4000 [38] on mouse MALAT1. Gapmer ASOs targeting human MALAT1 nts 6001-8000 [40] and mouse MALAT1 nts 1-2000 [34,42], 2001-4000 [39], 4001-6000 [38].…”
Section: Discussionmentioning
confidence: 95%
“…For future investigations, it may be advantageous to design an LNA mixmer composed of natural and chemically modified nucleosides so that the increased flexibility can achieve greater stability of the MALAT1 and MENβ RNA•LNA-RNA triple helices along the Hoogsteen and Watson-Crick interfaces. [32,46], 4001-6000 [38,45] and nts 2001-4000 [38] on mouse MALAT1. Gapmer ASOs targeting human MALAT1 nts 6001-8000 [40] and mouse MALAT1 nts 1-2000 [34,42], 2001-4000 [39], 4001-6000 [38].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations